Fe-Mn-Si-O-S系合金の固液共存状態におけるMnO-SiO2系介在物上のMnS析出挙動 - Gamutan, Jonah; Miki, Takahiro; Nagasaka, Tetsuya (Nippon Tekko Kyokai, 2022)
With the emerging significance of creating an acicular ferrite microstructure to provide an optimum set of properties in steel, MnS precipitation behavior on a MnO-SiO2 inclusion at the solid-liquid coexistence temperature was experimentally investigated and thermodynamically elucidated in this study. Using a direct method of forming inclusions, alloy samples with varying sulfur concentrations [Fe-1.1Mn-0.10Si-0.05O-S (initial mass %); 0.005 to 0.031 initial mass % S] were prepared by holding at the solid-liquid coexistence temperature for 1 hour.